A RARE COMBINATION OF FETAL MACERATION AND PYOMETRA IN A TEN-YEAR-OLD CANINE: A SURGICAL PERSPECTIVE - Parkinson, TJ; Parkinson, TJ (International Journal of Allied Sciences (IJAS), 2022)
Fetal maceration and pyometra are rare conditions that can occur simultaneously in older, unsterilized female dogs. Fetal maceration occurs when an aborting fetus fails to be expelled, leaving fetal bones in the uterus. Pyometra, on the other hand, is a severe bacterial infection of the uterus, which can cause systemic illness, toxaemia, or septicemia in affected dogs. This report describes a rare case of fetal maceration along with simultaneous pyometra in a ten-year-old Labrador retriever bitch. The animal presented with a history of loss of appetite and foul-smelling vaginal discharge for 15 days. Trans-abdominal ultrasonographic examination revealed irregular hypoechoic pouches in the uterus, and pus discharge was observed upon incision of the uterus. Fetal bones were found scattered inside the uterus and uterine horns, causing severe inflammatory reactions and damage to the uterine wall. Ovariohysterectomy was performed, and the whole genitalia was removed. The authors attributed the condition to bacterial infections that may have caused pyometra. The document concludes that ovariohysterectomy is the best surgical approach when pyometra and fetal maceration occur simultaneously and cause severe damage to the uterus.